The roughening transition of the three-dimensional Ising interface: a Monte Carlo study - Hasenbusch, Martin; Meyer, Steffen; Pütz, Mathias (Journal of statistical physics, 1996)
We study the roughening transition of an interface in an Ising system on a 3D simple cubic lattice using a finite-size scaling method. The particular method has recently been proposed and successfully tested for various solid-on-solid models. The basic idea is the matching of the renormalization-groupflow of the interface with that of the exactly solvable body-centered cubic solid-on-solid model. We unambiguously confirm the Kosterlitz-Thouless nature of the roughening transition of the Ising interface. Our result for the inverse transition temperatureKr=0.40754(5) is almost two orders of magnitude more accurate than the estimate of Mon, Landau, and Stauffer.
Gesehen am 12.07.2022